A Comparison of Paleo-Eskimo and Medieval Norse Bone Fat Exploitation in Western Greenland - Outram, Alan K (The University of Wisconsin Press, 1999)
Reproduced with permission of the publisher. Details of the original publication are available at http://www.wisc.edu/wisconsinpress/journals/journals/aa.html The importance of fat in the diet is outlined. The practice of rendering animal bones for their grease content is discussed. A methodology for identifying levels of bone fat exploitation, based upon the analysis of bone fragmentation and bone fracture type, is described. Four Greenlandic sites are analyzed using these methods. Two of these, Sandnes (V51) and Niaquussat (V48), are Medieval Norse sites. The others, Qeqertasussuk and Itivnera, are Paleo-Eskimo sites of the Saqqaq culture. In both cultures, land mammal bone was heavily processed for bone fat while seal bones were not. Reasons for this are discussed. The relative levels of bone fat exploitation within these two cultures are contrasted. This study of bone fat exploitation is compared to one based upon the study of fat-loving diptera. The effect that differential levels of bone rendering could have upon bone assemblage quantification is outlined.